End point prick test: could this new test be used to predict the outcome of oral food challenge in children with cow's milk allergy? - Bellini Federica; Ricci Giampaolo; Dondi Arianna; Piccinno Valentina; Angelini Federico; Pession Andrea (BMC, 2011)
Abstract Background Cow's milk allergy (CMA) is the most frequent food allergy in childhood; the trend of CMA is often characterized by a progressive improvement to achieve tolerance in the first 4 to 5 years of life. It has been observed that specific IgE (sIgE) towards cow's milk proteins decrease when the age increases. Although food allergy can be easily diagnosed, it is difficult to predict the outcome of the oral food challenge (OFC), that remains the gold standard in the diagnosis of food allergy, by allergometric tests. Methods We considered 44 children with CMA diagnosed through OFC who returned to our Allergy and Immunology Pediatric Department between January to December 2010 to evaluate the persistence of allergy or the achievement of tolerance. On the basis of the history, we performed both allergometric skin tests and OFC in children that were still following a milk-free diet, whereas only allergometric skin tests those that had already undergone spontaneous introduction of milk protein at home without presenting symptoms. Objective The aim of this study was to investigate the relationship between the persistence of CMA or the acquisition of tolerance and the results of the end point prick test (EPT). Results and Discussion The OFC with cow's milk was performed on 30 children, 4 children were excluded because of a history of severe reactions to cow's milk, and 10 because they had spontaneously already taken milk food derivates at home without problems. 16/30 (53%) children showed clinical reactions and the challenge was stopped, 14/30 (47%) did not have any reaction. Comparing the mean wheal diameter of every EPT's dilution between the group of allergic children and the tolerant ones, we obtained a significant difference (p < 0.05) for the first 4 dilutions. We have also calculated sensitivity (SE), specificity (SP), the positive predictive value (PPV) and the negative predictive value (NPV) for each EPT dilution. Conclusions EPT is a safe and cheap test, easy to be executed and that could provide good prediction of the outcome of OFC; so it might be used to avoid OFC-induced anaphylaxis in children affected by CMA. It can also help avoiding dietetic restrictions in tolerant children who show sensitization towards cow's milk proteins.